Activities of BMS 284756 (T-3811) against Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus pneumoniae Isolates from SENTRY Antimicrobial Surveillance Program Medical Centers in Latin America (1999) - Gales, Ana (American Society for Microbiology, 2001)
The antimicrobial activity of BMS 284756, a novel des-F(6)-quinolone, was comparatively evaluated against 257 Streptococcus pneumoniae, 198 Haemophilus influenzae, and 88 Moraxella catarrhalis strains isolated in Latin America between July and September of 1999 as part of the SENTRY Antimicrobial Surveillance Program. Nearly 28.0% of S. pneumoniae strains were nonsusceptible to penicillin. The rank order of quinolone potency versus S. pneumoniae was BMS 284756 (MIC at which 90% of isolates were inhibited [MIC(90)], 0.12 μg/ml) > trovafloxacin (MIC(90), 0.25 μg/ml) > gatifloxacin (MIC(90), 0.5 μg/ml) > levofloxacin and ciprofloxacin (MIC(90), 1 to 2 μg/ml). All S. pneumoniae strains that were not susceptible to other quinolones were inhibited by BMS 284756 at ≤2 μg/ml. The overall prevalence of β-lactamase production was 15.2% in H. influenzae and 98.9% in M. catarrhalis. BMS 284756 showed excellent potency and spectrum against this group of pathogens, inhibiting all isolates at ≤0.12 μg/ml. BMS 284756 exhibited activity similar to those displayed by the new fluoroquinolones, such as levofloxacin, trovafloxacin, or gatifloxacin, and could be a therapeutic option for empirical treatment of community-acquired respiratory tract infections.